(untitled) (World Economics and Finance Bulletin, 2026)
The present study aimed to identify the extent to which the dimensions of behavior modeling for managers are employed in a number of cement factories in Sulaimaniyah Governorate. The problem of the study came through the continuous environmental challenges witnessed by the cement industry sector in the Iraqi environment, including complexity and high red tape in work procedures, as well as the existence of economic problems related to ownership and financing that affected the salaries of workers in the field. In order to achieve the objectives of the current study, the researchers adopted in their study the descriptive-analytical approach in presenting theoretical and conceptual frameworks, and processing, analyzing, and interpreting data. This method suits the study of behavioral and administrative phenomena, and determined the field of the current study in the cement factories in Sulaymaniyah Governorate, represented by (Almas, Bazian, Delta, Mullawi, Jasin). The population of the present study was all the managers working in this assistantship and its laboratories (formation managers, heads of departments, and division officials), which are (480), while the sample of the current study reached (214) managers, and for the purpose of testing the hypotheses of the study and confirming their validity. The study used a number of statistical methods and tools in analyzing the data, and processing them with the aim of reaching the opinions of individuals in the researched field towards the questionnaire paragraphs, and through statistical treatment. The study found two correlation and inverse significant effects between managers’ behavior modeling and organizational collapse in the studied field.